Portable, Battery-Operated, Low-Cost, Bright Field and Fluorescence Microscope - Miller, Andrew R. (Public Library of Science, 2010)
This study describes the design and evaluation of a portable bright-field and fluorescence microscope that can be manufactured for $240 USD. The microscope uses a battery-operated LED-based flashlight as the light source and achieves a resolution of 0.8 µm at 1000× magnification in fluorescence mode. We tested the diagnostic capability of this new instrument to identify infections caused by the human pathogen, Mycobacterium tuberculosis. Sixty-four direct, decontaminated, and serially diluted smears were prepared from sputa obtained from 19 patients suspected to have M. tuberculosis infection. Slides were stained with auramine orange and evaluated as being positive or negative for M. tuberculosis with both the new portable fluorescence microscope and a laboratory grade fluorescence microscope. Concordant results were obtained in 98.4% of cases. This highly portable, low cost, fluorescence microscope may be a useful diagnostic tool to expand the availability of M. tuberculosis testing at the point-of-care in low resource settings.